2013
DOI: 10.1038/aps.2012.198
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine induction of theta frequency oscillations in rodent medial septal diagonal band in vitro

Abstract: Aim: This study aimed to examine the role of the nicotinic receptor (nAChR) in the generation of theta oscillations (4-12 Hz) in vitro. Methods: Electrophysiological studies were performed on medial septal diagonal band area (MSDB) slices to measure theta oscillation. Immunofl uorescence and confocal microscopy studies were carried out to detect α4 nAChR and β2 nAChR subunits in perfused-fi xed tissue from VGluT2-GFP and GAD67-GFP transgenic mice. Results: Application of nicotine to MSDB slices produced persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 44 publications
7
15
0
Order By: Relevance
“…Our results indicate that in the presence of DhβE but not MLA, nicotine+DHPG failed to induce γ oscillation, suggesting that α4β2 nAChR plays a more important role than α7 nAChR in mediating the oscillatory activity of MSDB, which is in line with our previous observation that α4β2 nAChR mediated nicotine-induced θ activity in the MSDB [24] . Our results further demonstrated that the induced γ oscillation is dependent on excitatory and inhibitory neurotransmission based on the roles of AMPA receptor and GABA A receptor blockers, which is in agreement with previous reports [26,27] .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our results indicate that in the presence of DhβE but not MLA, nicotine+DHPG failed to induce γ oscillation, suggesting that α4β2 nAChR plays a more important role than α7 nAChR in mediating the oscillatory activity of MSDB, which is in line with our previous observation that α4β2 nAChR mediated nicotine-induced θ activity in the MSDB [24] . Our results further demonstrated that the induced γ oscillation is dependent on excitatory and inhibitory neurotransmission based on the roles of AMPA receptor and GABA A receptor blockers, which is in agreement with previous reports [26,27] .…”
Section: Discussionsupporting
confidence: 92%
“…The present study extends our previous investigations [15,16,22] on the contribution of nAChR and mGluR1 to the control of θ and γ oscillations in the MSDB. Specifically, we demonstrated that co-activation of mGluR1 and nAChR can control the pattern of network oscillation in MSDB through the combination of various concentrations of two receptor agonists, DHPG and nicotine.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations